Struktur Skeleton Sirip Kaudal Kompleks Periophthalmus gracilis - Gatot Nugroho Susanto; Fransisca Ressa Utari (Biogenesis: Jurnal Ilmiah Biologi, 2016)
Cauda of Periophthalmus gracilis rarely used for locomotion in land. The objective is to know skeleton structure of caudal fin complex. Skeleton staining used Alizarin red’s-alcian blue modified from Inouye (1976). Periophthalmus gracilis’s caudal fin complex have 8 os preural centrum, 2 os epural, os parhypural, 5 os hypural and branched lepidotrichia. The caudal used to support movement in land. Periophthalmus gracilis used it for balancing and support in land.